ASPİRASYON VE %3 SODYUM TETRADECYL SULFATE İLE SKLEROTERAPİNİN HİDROSEL TEDAVİSİNDEKİ ETKİNLİĞİ - ÖNDER, Ali Ulvi; ALAN, Cabir; ÖNER, Armağan; SOLOK, Vural; KALKAN, Mehmet; UZUN, Hakkı (Cerrahpaşa Medical Journal, 2019)
Backround And Design.- We evaluated the success, complications and cost-effectiveness of aspiration and schlerotherapy in treatment of hydrocele. Between December 1998 and March 2001 we performed aspiration and schlerotherapy in 38 patients and 40 hydrocele cases. 16-18 canule was used for aspiration, then schlerosant agent (%3 sodium tetradecyl sulphate) mixed with saline and anesthesic drug was given through the same canule . Patients used prophilactic antibiotic after the procedure. We followed up the patients with physical examination 2, 6 months and yearly. Results.- Mean patient age was 45,7 (17-72) years, follow up period was 31,9 (12,3-46,7) months and the measured mean aspirated hydrocele volume was 192,5 cc (50-520). We repated the tratment for 15 of 21 cases which recurrence was seen. 26 of 40 (%65) hydrocele aspiration was successful. The success rates for the aspirated volume below and above 150 cc were found %67,8 and %25,9 respectively, and statistically significant (chi square -p=0,02). In 2 patients postprocedure inguinal pain was controlled with NSAID and epydidymitis was diagnosed in 1 patient. In cytologic examination no malignant cells were present and positive cultures were noted in only 2 patients. Costs of hydrocelectomy, aspiraton -schlerotherapy and second procedure were 450 ,80, 80,80, and 30 respectively.Thetotalcostintheschlerotherapygroup:totalcostof(firstprocedure+secondprocedure+failedcases(ifsurgeryperformed))is(40x80respectively. The total cost in the schlerotherapy group: total cost of (first procedure + second procedure + failed cases (if surgery performed)) is (40 x 80respectively.Thetotalcostintheschlerotherapygroup:totalcostof(firstprocedure+secondprocedure+failedcases(ifsurgeryperformed))is(40x80) + (15 x 30 )+(14x450) + (14 x 450)+(14x450) = 9950 . This result which we found was 55,3 % of the total cost of 40 hydrocelectomies (40 x 450 = 18000 ). Conclusıon.- Aspiration and schlerotherapy is the first choice of treatment because of its success, easily performability, low morbidity and cost-effectiveness.